Peran Pemerintah Kabupaten Pandeglang dalam Edukasi Mitigasi Bencana Tsunami di Sekolah Pesisir Pantai Pandeglang - Banten - Yuningsih Yuningsih; Wika Hardika Legiani; Febrian Alwan Bahrudin (Universitas Batanghari Jambi, 2022)
Indonesia is located between 3 tectonic plates, which are the Pacific plate, the Indo-Australian plate, and the Eurasian plate. These 3 plates can collide with each other and can cause earthquakes and tsunamis, based on BNPB data, and in the Indonesia Disaster Risk Index (known as IRBI), Banten province is included in the high-risk class for disasters, including tsunami disasters. The location of the current research was carried out at SMA Negeri 3 Pandeglang and SMA Negeri 15 Pandeglang which were on the coast that were prone to tsunami disasters. The purpose of this study was to describe the relationship between government and schools in tsunami disaster preparedness. This study used a qualitative approach with a descriptive method. Data collection techniques consisted of observation, interviews and documentation. Based on the research results, it is known that the government could demonstrate its role in disaster management through 4 (four) ways, which were legislation, institutions, planning, and capacity building. The results showed that the Pandeglang Regency Government in this case the Pandeglang Regency BPBD was quite successful in Tsunami Disaster Mitigation Education at the Pandeglang Coastal School Banten. In carrying out disaster risk reduction efforts, the Pandeglang Regency Government had a legal basis and was also able to formulate disaster mitigation strategies in schools, which were the establishment of Disaster Resistant Schools (known as STB) and the formation of the Pandeglang Regency Regional Disaster Management Task Force (known as PBD.